2009
DOI: 10.1007/s11104-009-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro-analytical, physiological and molecular aspects of Fe acquisition in leaves of Fe-deficient tomato plants re-supplied with natural Fe-complexes in nutrient solution

Abstract: It is well known that in the rhizosphere soluble Fe sources available for plants are mainly a mixture of complexes between the micronutrient and organic ligands such as organic acids and phytosiderophores (PS) released by roots, microbial siderophores as well as fractions of humified organic matter. In the present work, mechanisms of Fe acquisition operating at the leaf level of plants fed with different Fe-complexes were investigated at the micro-analytical, physiological and molecular levels. Fe-deficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Although the fate of the siderophore has not been evaluated yet, the similar efficiency of the organic and chemical agents appears as a promising alternative to reduce chemical inputs due to Fe chemical fertilization (Orera et al 2009). A positive side effect was also observed for N, P, K and Na, indicating that a fast recovery of nutrients was occurring in BS-treated plants (Nikolic et al 2007); this was specially marked for N, consistent with growth parameters, and, therefore, could have an impact in the nutritional quality of edible parts of plants (Briat et al 2007; Tomasi et al 2009). Since the siderophore was provided to plants with Fe, effects should only refer to this ion.…”
Section: Discussionmentioning
confidence: 95%
“…Although the fate of the siderophore has not been evaluated yet, the similar efficiency of the organic and chemical agents appears as a promising alternative to reduce chemical inputs due to Fe chemical fertilization (Orera et al 2009). A positive side effect was also observed for N, P, K and Na, indicating that a fast recovery of nutrients was occurring in BS-treated plants (Nikolic et al 2007); this was specially marked for N, consistent with growth parameters, and, therefore, could have an impact in the nutritional quality of edible parts of plants (Briat et al 2007; Tomasi et al 2009). Since the siderophore was provided to plants with Fe, effects should only refer to this ion.…”
Section: Discussionmentioning
confidence: 95%
“…In our experiment, the increase observed in leaf Fe concentration from aliphatic amino acid-treated plants might have favoured the formation of Fe-phytosiderophore complexes and enhanced the xylem transport and phloem translocation of Fe (Robin et al, 2008) rather than induced changes in the pH of the nutrient solution, since it remained constant during the experimental period (5.5-6.5). Tomasi et al (2009) observed that Fe acquisition through roots in tomato plants depends on the nature of Fe-complexes, whereby Fe complexed to a water-extractable humic substances fraction has higher rates of reduction and uptake than Fe complexed with siderophores. Aliphatic amino acidinduced also enhancements in leaf Mn and Cu concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, 21-d-old Fe-defi cient cucumber plants were grown for further 11 d in nutrient solution (renewed every 3 d, pH buff ered at 7.5 with 10 mM HEPES and divided into the following treatments: (i) not supplied with any exogenous Fe sources (-Fe control); (ii) supplied with Fe-o,oEDDHA; (iii) supplied with sample A that was characterized by Fe complexed to poorly soluble high-molecular-weight HS (Fe-IHS); (iv) supplied with Fe complexed to a soluble water humifi ed organic fraction (Fe-WEHS) containing mostly fulvic substances of low molecular weight extracted from sphagnum peat (<1 kDa; Pinton et al, 1997a) and widely characterized for its contribution to the Fe acquisition by Strategy I plants (Pinton et al, 1999;Cesco et al, 2002;Tomasi et al, 2009). Th e Fe-IHS complex A was stored under stirring to limit the Fe association with HS forming a humic network; this procedure does not change the colloidal state of the complex with aging.…”
Section: Iron Uptake From Iron-insoluble Humic Substance Complexes Bymentioning
confidence: 99%